2001
DOI: 10.1210/jcem.86.5.7506
|View full text |Cite
|
Sign up to set email alerts
|

β1- andβ2-Adrenoceptor-Mediated Thermogenesis and Lipid Utilization in Obese and Lean Men1

Abstract: The aim of this study was to elucidate the roles of the beta(1)- and the beta(2)-adrenoceptors in thermogenesis and lipid utilization in obesity. The beta(1)-adrenoceptor study was performed in 9 obese and 10 lean men and consisted of 4 30-min periods during which subjects received consecutive infusions of 0, 3, 6, and 9 microg/kg fat-free mass (FFM).min dobutamine. Energy expenditure, lipid oxidation, and plasma nonesterified fatty acids and glycerol concentrations increased similarly in both groups during be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…Interestingly, both effects can be observed in catecholamine‐induced insulin resistance. Thus, we and others have shown that β‐adrenergic stimulation leads to increased serum concentrations of FFA and inhibits insulin signaling molecules essential for insulin action such as insulin receptor substrates [25,28–30]. It appears possible that reduced expression of adiponectin contributes to increased FFA levels and impaired insulin signaling after chronic catecholamine treatment.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, both effects can be observed in catecholamine‐induced insulin resistance. Thus, we and others have shown that β‐adrenergic stimulation leads to increased serum concentrations of FFA and inhibits insulin signaling molecules essential for insulin action such as insulin receptor substrates [25,28–30]. It appears possible that reduced expression of adiponectin contributes to increased FFA levels and impaired insulin signaling after chronic catecholamine treatment.…”
Section: Discussionmentioning
confidence: 84%
“…It appears possible that reduced expression of adiponectin contributes to increased FFA levels and impaired insulin signaling after chronic catecholamine treatment. However, direct effects of β‐adrenergic activation on lipolysis and insulin signaling molecules most likely also contribute [23–25,30].…”
Section: Discussionmentioning
confidence: 99%
“…β‐Adrenoceptor blockade by propranolol has been shown to reduce 24 h fat oxidation (17,18). The increase in relative fat oxidation is found after selective stimulation of β1‐adrenoceptors by dobutamine (22) as well as after selective β2‐adrenoceptor stimulation by salbutamol (23) (Fig. 1).…”
Section: The Peripheral Sympathetic Nervous System and Energy Balancementioning
confidence: 89%
“…α‐Adrenoceptors do not appear to play a role in the thermogenic effect of sympathetic nervous system activity (19). Stimulation of β1‐ as well as β2‐adrenoceptors cause increased energy expenditure (19–23). Whether the β3‐adrenoceptor plays a significant role in human thermogenesis remains unclear.…”
Section: The Peripheral Sympathetic Nervous System and Energy Balancementioning
confidence: 99%
“…In the present study, we were able to examine only one receptor subtype in one thermogenic tissue, that is, skeletal muscle, where only the β 2 ‐AR subtype is expressed (Liggett et al 1988; Martin et al 1992; Jensen et al 1995 a ). The β 2 ‐AR subtype has been shown to contribute significantly to β‐AR‐mediated thermogenesis, since appreciable increases in EE are observed during administration of isoproterenol with co‐infusion of the selective β 1 ‐AR antagonist atenolol (Blaak et al 1993), and also during selective β 2 ‐AR stimulation with salbutamol (Schiffelers et al 2001; Oomen et al 2005). It is possible that the density of other β‐AR subtypes in other thermogenic tissues may differ in exercising and sedentary humans and may play a role in differences in the whole‐body thermogenic response to β‐AR stimulation.…”
Section: Discussionmentioning
confidence: 99%